Gradual Wage-Price Adjustments, Labour Market Frictions and Monetary Policy Rules - Christian Proa\~no Acosta (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2007)
Contrary to the assumption of perfectly flexible labour markets commonly used in mainstream macroeconomic models, in the real world the existence of structural imperfections such as search and trading costs hinder the frictionless functioning of these markets, generally leading to outcomes of Non-Walrasian type with involuntary unemployment and open vacancies in "equilibrium". In this paper the author models the existence of labour market frictions into a Keynesian (Disequilibrium) AS-AD framework in the line of Asada, Chen, Chiarella and Flaschel (2006) through a labour search and matching function. By means of dynamic shock simulations, the author finds that the extent of the labour market rigidity has a great importance for the dynamics not only of employment and output, but also of wage and price inflation, and consequently also for the conduction of monetary policy.
urn:nbn:de:101:1-2008081888
Keywords: E31; E52; 330; Labour market frictions; staggered wage and price dynamics; (D)AS- AD; monetary policy